Implementation of a Low- Cost Multi- IMU by Using Information Form of a Steady State Kalman Filter - A. M. Shahri; R. Rasoulzadeh (AUT Journal of Electrical Engineering, 2017)
In this paper, a homogenous multi-sensor fusion method is used to estimate the trueangular rate and acceleration with a combination of four low cost (< 10$) MEMS Inertial MeasurementUnits (IMU). An information form of steady state Kalman filter is designed to fuse the output of four lowaccuracy sensors to reduce the noise effect by the square root of the number of sensors. A hardware isimplemented to test the method with three types of experiments: static test, constant rate, and oscillatingtest. Results of static test for z-axis show that ARW coefficient reduces to 0.0022°/√s and VRW error isdecreased by %50. Also, dynamic test results show the reduction of the standard deviation of combinedrate signal up to six times compared with a single sensor. A comparison between the proposed filter andthe simple averaging method is made in which the results indicate that the Kalman filter is more accuratecompared to the averaging method.